농업용 포크리프트의 구동력 및 운동저항 예측을 위한 모델링 기법 개발 - 조재현(Jae-hyun Jo); 김준태(Jun-tae Kim); 정진형(Jin-hyoung Jeong); 장영윤(Young-yoon Chang); 박원엽(Won-yeop, Park); 이상식(Sang-sik Lee) (한국정보전자통신기술학회 논문지, 2019)
This study was initiated to solve the difficulties of aged and female workers in agriculture society due to aging and demise of young people. In the case of the conventional elevated lift, the risk of exposure to uneven road or work environment, not the difficulty of professional qualification and operation, and the risk of exposure to the uneven road or working environment, were also studied based on previous researches so that women could easily and efficiently perform productive agriculture. First, the simulation was carried out through the prediction model of traction performance using the object of agricultural forklift, and the soil of the Kimhae city in Gyeongnam (34.125kPa, internal friction angle 35.294deg, external friction angle 13.620deg, Adhesion force 5.750 kPa, average cone index 0-15 cm cl, 1001.8 kPa). In the case of the forklift for simulation, the driving force and the kinetic resistance prediction modeling of the agricultural electric forklift are modeled. Based on this model, the motor control drive adopts the 1232E model, which is a drive dedicated to AC motor, and divides the two drivers into master and slave And the model for the simulation was designed to control motor drive, hydraulic drive, and various outputs on the main PCB. The simulation model is undergoing continuous simulation, modification and supplementation. Based on this research, we will continue research for development of safer and more efficient agricultural electric forklift. 본 연구는 고령화와 젊은층의 이탈로 인한 농경사회에서 고령 및 여성 인력의 애로사항을 해결해주기 위해 시작되었다. 기존에 나와있는 농업용 고소리프트의 경우 전문 자격증 및 조작의 어려움과 평지가 아닌 불균형적인 도로 혹은 작업환경에 노출된 위험성과 여성들도 쉽고 효율적으로 생산적 농업을 할 수 있도록 하기 위하여 선행연구를 바탕으로 진행하였다. 먼저 농업용 포크리프트의 목적인 물체를 이용한 견인 성능 예측 모델을 통하여 시뮬레이션을 진행하고, 견인 성능 모델 수식을 이용하여 실험이 진행되고 있는 경남 김해시의 토양(점착력 34.125kPa, 내부마찰각 35.294deg, 외부마찰각 13.620deg, 부착력 5.750kPa, 평균 원추지수 0-15cm cl, 1001.8kPa)에 맞추었다. 시뮬레이션용 포크리프트의 경우 농업용 전동식 포크리프트의 구동력 및 운동저항 예측 모델링을 수식화하고 이를 바탕으로 모터 제어 드라이브는 AC모터 전용 드라이브인 1232E 모델을 적용, 프로그래밍을 통해 두 개의 드라이버를 각각 마스터와 슬레이브로 구분지어 구동할 수 있도록 하였고 메인 PCB에는 모터구동, 유압구동, 각종 출력을 제어할 수 있도록 시뮬레이션용 모델을 제작하였다. 제작된 시뮬레이션용 모델은 현재 지속적인 시뮬레이션과 수정 및 보완을 진행하고 있으며, 추후 본 연구를 바탕으로 보다 안전하고 효율성이 뛰어난 농업용 전동식 포크리프트의 개발을 위하여 연구를 지속할 예정이다.